(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Necessity, timeliness and significance of thelearning and teaching system Learning for Life, grounded on self-directed learning, are actualised by the lack of systematic approach to bullying prevention in Lithuania, lack of prevention of bullying due to learning differences and experience and situation of bullying prevention in the country that has formed in this context. Currently bullying cases are increasingly often spoken of but it has to be acknowledged that interest in this problems is taken more episodically, quite often reacting to resonant bullying cases. This demonstrates that the systemic approach is still missing, that the real scope of spread of bullying, its reasons, consequences have not yet been perceived and this aggravates possibilities to manage the situation. Prevention of bulling arising at school due to learning differences should be based on the learning and teaching system Learning for Life, grounded on self-directed learning and acknowledgement of the learners learning differences, characteristic to it, and not on the perception of differences as stigmatising shortcoming. In the article by using the method of content analysis, abstraction actualised necessity, timeliness and significance of selfdirected learning framework for the prevention of school bullying of these criteria : links of the system "Learning for Lifewith European and national education documents on education; the education system "Learning for Life interface with methodological approaches; pronciples of the system "Learning for life" as fundamental approaches; the aspects of manifestation of the education system "Learning for life"concept in the educational practice.